Coaxial pulsed 3 MW RF power input for 176 MHz accelerating structure - Auslender, V.L.; Chernov, K.N.; Gornakov, I.V.; Kazarezov, I.V.; Makarov, I.G.; Matyash, N.V.; Ostreiko, G.N.; Panfilov, A.D.; Serdobintsev, G.V.; Tarnetsky, V.V.; Tiunov, M.A.; Shachkov, V.E. (Вопросы атомной науки и техники, 2008)
Design of the power input is described in the paper. The power input is a low-impedance coaxial line with the wave resistance of about 30 Ohm. One of the line ends is shorted, the other turns into the coupling loop, which inductance is compensated by the stray capacitance. The vacuum section of the power input is separated from the atmosphere by the cylindrical insulator made of 22XC ceramics. The coaxial part of the power input is divided into the 176 MHz quarter-wave-length insulator and quarter-wave-length transformer by the point of the 50 Ohm RF power feeder connection. Power input testing technique is described in the paper together with the results obtained when operating at the high power level. Наведено конструкцію вводу потужності, що являє собою низькоомну коаксіальну лінію з хвильовим опором порядку 30 Ом. Один кінець лінії закорочено, а інший переходить у петлю зв'язку, індуктивність якої компенсована конструктивною ємністю. Вакуумна частина вводу потужності відділена від атмосфери циліндричним ізолятором з кераміки 22ХС. Високочастотна потужність підводиться фідером до місця, що розділяє коаксіальну частину вводу на чвертьхвильовий ізолятор і чвертьхвильовий трансформатор на частоті 176 МГц. Хвильовий опір фідера, що підводить потужність, 50 Ом. Описано методику випробування вводу потужності на стенді, наведені результати його роботи на великому рівні потужності. Приведена конструкция ввода мощности. Он представляет собой низкоомную коаксиальную линию с волновым сопротивлением порядка 30 Ом. Один конец линии закорочен, а другой переходит в петлю связи, индуктивность которой компенсирована конструктивной емкостью. Вакуумная часть ввода мощности отделена от атмосферы цилиндрическим изолятором из керамики 22ХС. Высокочастотная мощность подводится фидером в месте, разделяющем коаксиальную часть ввода на четвертьволновый изолятор и четвертьволновый трансформатор на частоте 176 МГц. Волновое сопротивление подводящего мощность фидера 50 Ом. Описана методика испытания ввода мощности на стенде, приведены результаты его работы на большом уровне мощности.